String matching algorithms: to search and compare longest common subsequence strings retrieved from Wagner & Fischer and Hirschberg algorithms on Malay dictionary words / Mohd Razif Mohd Ghazi - Mohd Ghazi, Mohd Razif (1999)
Information Technology has enabled information that can be in many forms such as text, image or sound, to be accessed widely using search terms via a computer. Due to this type of popularity and advancement in technology, there is an increased interest in searching Malay text to enable scholars and researchers to access the data on-line. This thesis studies the method of a string searching algorithm. There are two methods being evaluated in this research. These are the Wagner & Fischer and Hirschberg algorithms. These methods were chosen because they are based on dynamic programming. Dynamic programming is used to solve both the String Distance Problem and Longest Common Subsequence (LCS) problem. The results obtained shows searching and comparison of LCS retrieved by both algorithms. Comparing of words is carried out based on Dice coefficient.